Neurodivergent inclusivity within the supervisory relationship: Co-creating shared meaning using CMM - Stark, Eloise; Helps, Sarah (Murmurations: Journal of Transformative Systemic Practice, 2026)
We describe the beginnings of an ongoing collaboration between two curious clinicians seeking to deconstruct in order to co-construct meaning brought to the supervisory relationship in the context of difference, specifically neurodivergence. With different spoken relationships to neurodivergence between us, among many other intersections of our identities, we were asked to create and deliver a supervisor training workshop for clinicians supervising clinical psychologist trainees. We write this paper to share some of our journey together, expressed through reflections on our workshop and the co-constructed meaning that arose from bringing our conversations to a wider audience. Our hope is to tell a story of how Coordinated Management of Meaning (CMM) theory and practices can support speaking about, around, of, or with difference in supervisory relationships. We conclude with a co-constructed model for use by supervisors in curiously considering the multiple intersecting influences upon a neurodivergent supervisee within an ongoing supervisory relationship. We hope to inspire greater curiosity and reflection on the application of CMM theory and skills to supporting difference, including neurodivergence, within supervisory relationships across clinical disciplines.